Designing a highly efficient polysulfide conversion catalyst with paramontroseite for high-performance and long-life lithium-sulfur batteries. (March 2019) - Wang, Sizhe; Liao, Jiaxuan; Yang, Xiaofei; Liang, Jianneng; Sun, Qian; Liang, Jianwen; Zhao, Feipeng; Koo, Alicia; Kong, Fanpeng; Yao, Yao; Gao, Xuejie; Wu, Mengqiang; et al.
Abstract: Numerous efforts have been made to design the cathode of Li–S batteries to enhance reversible capacity and long-term cycling stability. However, challenges remain in achieving high electronic/ionic conductivity and suppressing the shuttle effect, especially for cathodes with high sulfur loading. Here we report a 3D free-standing hierarchical structure of VO2 (P) (paramontroseite VO2 ) nanoparticles grown on nitrogen-doped carbon nanotube (NCNT) arrays as a catalytic host for high-performance sulfur cathodes. In this architecture, the VO2 (P) nanoparticles function as catalysts to oxidize the LiPS to produce thiosulfate due to the strong chemical interaction. Furthermore, thiosulfates act as a mediator to catenate long-chain LiPS together and convert short-chain Li2 S2 /Li2 S and surface-bound polythionate complexes. Accordingly, the VO2 (P)-NCNT/S cathode exhibits excellent performance with high discharge capacity output (≈1200 mA h g −1 at 0.2 C), stable long-term cycling (≈67% retention at 2 C for 500 cycles), and high sulfur loading cycling (initial areal capacity of 10.2 mA h cm −2 at 0.2 C for 200 cycles). This nanostructure catalytic cathode with high sulfur loadings, as well as stable cycling performances, is attractive for developing practically useable Li-S batteries. Graphical abstract: 3D free-standing hierarchical structure of VO2 (P) nanoparticles grown on nitrogen-doped carbon nanotube arrays as a catalytic host for sulfur cathodes. Detailed insight into the catalystic effect of VO2 (P) to transfer long-chain LiPS help to better designing the cathode for high-performance Li-S batteries. fx1 Highlights: Paramontroseite is the first to be introduced into Li-S batteries electrode. Unique 3D free-standing structure can accommodate the high sulfur loadings per unit area. Efficient Polysulfide Conversion Catalyst with paramontroseite were testified. Detailed insight into the mechanism of propelling polysulfide conversion by XANES spectra. Superior electrochemical performances with high areal capacity.